Carbon nanotube dispersion

JP2025026155APending Publication Date: 2025-02-21ZEON CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023131553
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-10
Publication Date
2025-02-21

AI Technical Summary

Benefits of technology

【0014】 本発明によれば、分散状態の経時安定性に優れるとともに、導電性に優れる成形体を形成可能なカーボンナノチューブ分散液を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025026155000001
    Figure 2025026155000001
  • Figure 2025026155000002
    Figure 2025026155000002
  • Figure 2025026155000003
    Figure 2025026155000003
Patent Text Reader

Abstract

To provide a carbon nanotube dispersion excellent in temporal stability of a dispersion state while capable of forming a molded body excellent in conductivity.SOLUTION: The carbon nanotube dispersion includes a plurality of carbon nano-tubes, a solvent and a thickener. The plurality of carbon nano-tubes include a monolayer carbon nano-tube. At least some of the plurality of carbon nano-tubes form a carbon nano-tube bundle. When the carbon nano-tube bundle is observed with a scanning electron microscope, an average length of the carbon nano-tube bundle is over 1.50 μm, and an average diameter of the carbon nano-tube bundle is 18.0 nm or less. The number of the carbon nano-tube bundles with a diameter over 30.0 nm is 15 or less, from among 100 carbon nano-tube bundles. When the carbon nano-tube bundle is observed with an optical microscope, an average length of the carbon nano-tube bundle is 8.0 μm or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a carbon nanotube dispersion liquid. [Background technology]

[0002] 2. Description of the Related Art Carbon nanotubes (hereinafter sometimes abbreviated as "CNTs") have been attracting attention as a material that has excellent properties such as electrical conductivity, thermal conductivity, and strength.

[0003] Although each CNT has excellent properties, it is easy to bundle (become a bundle) due to van der Waals force due to its small outer diameter. Therefore, it has been conventional to prepare a carbon nanotube dispersion (CNT dispersion) by dispersing CNTs in a solvent. The obtained CNT dispersion is used, for example, for the production of a molded product such as a carbon film formed by an assembly of multiple CNTs, or an electrode for a secondary battery.

[0004] Therefore, in recent years, attempts have been made to improve the properties of the molded body by improving the CNT dispersion liquid. For example, Patent Document 1 discloses a CNT dispersion that contains CNTs, a solvent, and a dispersant, and in which the average outer diameter of the CNTs, the half-width of the peak at a diffraction angle 2θ=25°±2°, and the G / D ratio are each within a predetermined range. According to Patent Document 1, the use of the CNT dispersion makes it possible to obtain a resin composition, an electrode film, and the like that are excellent in electrical conductivity. Patent Document 2 discloses a CNT dispersion that contains CNTs and a solvent, and in which the average outer diameter, BET specific surface area, and average fiber length of the CNTs are each within a predetermined range. According to Patent Document 2, the CNT dispersion can be used to obtain a resin composition, an electrode film, and the like that are excellent in electrical conductivity and adhesion. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2020 / 004095 [Patent Document 2] Patent Publication No. 2021-72279 Summary of the Invention [Problem to be solved by the invention]

[0006] However, in recent years, there has been a demand for further improvement in the properties of molded articles formed from CNT dispersions, and the conventional CNT dispersions have room for improvement in terms of further increasing the electrical conductivity of the molded articles and in terms of the stability of the dispersed state over time.

[0007] Therefore, an object of the present invention is to provide a carbon nanotube dispersion liquid that has excellent stability over time in the dispersed state and is capable of forming a molded body having excellent electrical conductivity. [Means for solving the problem]

[0008] The present inventor has conducted intensive research with the aim of solving the above problems. Here, the present inventor has focused on bundles formed by gathering a plurality of CNTs in a CNT dispersion (hereinafter, sometimes referred to as "CNT bundles"). The present inventor has found that, in a CNT dispersion containing a plurality of CNTs containing single-walled CNTs, a solvent, and a thickener, if the average length of the CNT bundles when observed with a scanning electron microscope (hereinafter, sometimes abbreviated as "SEM") is greater than a predetermined value, the average diameter of the CNT bundles is less than a predetermined value, the ratio of CNT bundles having a diameter of more than 30.0 nm is less than a predetermined value, and the average length of the CNT bundles when observed with an optical microscope is greater than a predetermined value, a CNT dispersion that has excellent stability over time in the dispersion state and can increase the conductivity of a molded body can be obtained, and the present invention has been completed.

[0009] That is, an object of the present invention is to advantageously solve the above problems, and according to the present invention, the following CNT dispersion liquids [1] to [4] are provided.

[0010] [1] A carbon nanotube dispersion comprising a plurality of carbon nanotubes, a solvent, and a thickener, wherein the plurality of carbon nanotubes include single-walled carbon nanotubes, at least a portion of the plurality of carbon nanotubes form carbon nanotube bundles, and when the carbon nanotube bundles are observed with a scanning electron microscope, the average length of the carbon nanotube bundles is greater than 1.50 μm, the average diameter of the carbon nanotube bundles is 18.0 nm or less, the number of carbon nanotubes having a diameter of greater than 30.0 nm is 15 or less out of 100 carbon nanotubes in the carbon nanotube bundles, and when the carbon nanotube bundles are observed with an optical microscope, the average length of the carbon nanotube bundles is 8.0 μm or more. A CNT dispersion containing a plurality of CNTs, including single-walled CNTs, a solvent, and a thickener, in which the average length of the CNT bundles exceeds a predetermined value, the average diameter of the CNT bundles is equal to or less than a predetermined value, and the number of CNT bundles having a diameter of more than 30.0 nm out of 100 CNT bundles is equal to or less than a predetermined value, and the average length of the CNT bundles is equal to or greater than a predetermined value when observed with an optical microscope, has excellent stability over time of the dispersed state and can provide a conductive film with excellent conductivity. In the present invention, the "average length of the CNT bundles," "average diameter of the CNT bundles," and "the number of CNT bundles with a diameter of more than 30.0 nm out of 100 bundles" when observed with an SEM, as well as the "average length of the CNT bundles" when observed with an optical microscope can each be measured using the methods described in the Examples of this specification.

[0011] [2] The carbon nanotube dispersion liquid according to [1] above, wherein the carbon nanotube bundles have an average aspect ratio of more than 100. When the average aspect ratio of the CNT bundles exceeds 100, the stability over time of the dispersed state of the CNT dispersion liquid can be further improved, and the electrical conductivity of the molded article can be further increased. In the present invention, the "average aspect ratio" of a CNT bundle can be determined by calculating the ratio of the average length to the average diameter (average length / average diameter) of the CNT bundle when observed with an SEM.

[0012] [3] The carbon nanotube dispersion liquid according to [1] or [2] above, wherein the G / D ratio of the carbon nanotubes is 0.5 or more and 120 or less. If the G / D ratio of the CNTs is within the above range, the stability over time of the dispersed state of the CNT dispersion liquid can be further improved, and the electrical conductivity of the molded article can be further increased. In the present invention, the "G / D ratio" refers to the ratio of the G band peak intensity to the D band peak intensity in a Raman spectrum, and can be measured by the method described in the Examples of this specification.

[0013] [4] The carbon nanotube dispersion liquid according to any one of the above [1] to [3], wherein the thickener comprises at least one selected from the group consisting of a cellulose-based polymer, a polycarboxylic acid, and a polyvinylpyrrolidone. When the thickener contains at least one selected from a cellulose-based polymer, a polycarboxylic acid, and a polyvinylpyrrolidone, the stability of the dispersed state of the CNT dispersion over time can be further improved, and the electrical conductivity of the molded article can be further increased. Effect of the Invention

[0014] According to the present invention, it is possible to provide a carbon nanotube dispersion liquid which is excellent in the stability of the dispersed state over time and is capable of forming a molded body having excellent electrical conductivity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, an embodiment of the present invention will be described in detail. Here, the CNT dispersion liquid of the present invention is not particularly limited, and can be used, for example, as a material for forming a molded body such as a carbon membrane or an elastomer molded body, an electrode for a secondary battery, and the like.

[0016] (Carbon nanotube dispersion) The CNT dispersion of the present invention contains at least CNTs, a solvent, and a thickener, and optionally contains components other than the CNTs, the solvent, and the thickener (other components). At least a portion of the multiple CNTs are single-walled CNTs, and form CNT bundles in the CNT dispersion. Here, the CNT dispersion of the present invention is characterized in that the average length of the CNT bundles when observed with an SEM exceeds 1.50 μm, the average diameter of the CNT bundles is 18.0 nm or less, the number of CNT bundles out of 100 having a diameter of more than 30.0 nm is 15 or less, and the average length of the CNT bundles when observed with an optical microscope is 8.0 μm. It should be noted that the CNT bundle is formed by assembling a number of CNTs into a bundle (bundle) along the longitudinal direction of the CNTs.

[0017] In addition, the CNT dispersion of the present invention has an average length of the CNT bundles greater than a predetermined value when observed with an SEM, an average diameter of the CNT bundles less than a predetermined value, the number of CNT bundles with diameters greater than 30.0 nm out of 100 bundles is less than a predetermined value, and the average length of the CNT bundles is greater than a predetermined value when observed with an optical microscope, so that the CNT dispersion has excellent stability over time in the dispersed state and can provide excellent electrical conductivity to the molded product. The reason why the above effects are obtained by using the CNT dispersion of the present invention is unclear, but is presumed to be as follows.

[0018] In order to improve the dispersibility of the CNT dispersion, the inventors focused on CNT bundles composed of multiple CNTs in the CNT dispersion. The smaller the average diameter of the CNT bundles, the fewer the number of CNTs constituting each bundle. Also, the fewer the number of CNTs with a diameter of more than 30.0 nm among 100 CNT bundles, the more the number of CNT bundles present in the CNT dispersion. And, in the CNT dispersion of the present invention, the average diameter of the CNT bundles is set to 18.0 nm or less, and the number of CNT bundles with a diameter of more than 30.0 nm among 100 CNT bundles is set to 15 or less, so that the number of CNT bundles present in the CNT dispersion is sufficiently secured. In addition, in the dispersion of the present invention, the average length of the CNT bundles when observed with an SEM is more than 1.50 μm, and the average length of the CNT bundles when observed with an optical microscope is 8.0 μm or more, so that the length of the CNT bundles present in the CNT dispersion is sufficiently secured. The reason why the average length of the CNT bundles is usually different between when observed with an SEM and when observed with an optical microscope is considered to be due to the following reasons. While a CNT bundle with a small diameter can be observed with an SEM with a high resolution, a CNT bundle with a small diameter cannot be observed with an optical microscope with a lower resolution than an SEM. Therefore, with an optical microscope, CNT bundles with a large diameter and length composed of a large number of CNTs tend to be selectively observed, and it is considered that the average length of the CNT bundles is different between when observed with an SEM and when observed with an optical microscope. And, in a CNT dispersion in which the number and length of CNT bundles are sufficiently secured as described above, CNTs are dispersed stably over time, and further, when such a CNT dispersion is used, CNT bundles with a sufficient length are distributed in the molded body, and a good conductive path can be formed. For the reasons described above, it is believed that the CNT dispersion of the present invention has excellent stability of the dispersed state over time, and that the use of this CNT dispersion can enable a conductive film to exhibit excellent conductivity.

[0019] <cnt> The CNTs are not particularly limited as long as they contain single-walled CNTs. As the CNTs, only single-walled CNTs may be used, or a combination of single-walled CNTs and multi-walled CNTs may be used.

[0020] <<Properties>> [Average length as observed by SEM] The average length of the CNT bundles observed by SEM must be more than 1.50 μm, preferably 1.60 μm or more, more preferably 1.70 μm or more, even more preferably 1.80 μm or more, even more preferably 1.90 μm or more, and particularly preferably 2.00 μm or more. If the average length of the CNT bundles observed by SEM is 1.50 μm or less, the conductivity of the molded body decreases. In addition, the upper limit of the average length of the CNT bundles observed by SEM is not particularly limited, and can be, for example, 3.50 μm or less, and can be 3.00 μm or less.

[0021] [Average length as observed under an optical microscope] The average length of the CNT bundles observed under an optical microscope must be 8.0 μm or more, preferably 10.0 μm or more, more preferably 12.0 μm or more, and even more preferably 15.0 μm or more. If the average length of the CNT bundles observed under an optical microscope is less than 8.0 μm, the conductivity of the molded body decreases. In addition, the upper limit of the average length of the CNT bundles observed under an optical microscope is not particularly limited, and can be, for example, 30.0 μm or less, 25.0 μm or less, or 20.0 μm or less.

[0022] Generally, the average length of a CNT bundle observed with an optical microscope is greater than the average length of a CNT bundle observed with an SEM. The average length of the CNT bundles in the CNT dispersion can be adjusted, for example, by changing the length of the raw CNTs (CNTs used as raw materials when preparing the CNT dispersion) and the conditions of the dispersion process. For example, when a wet jet mill is used for the dispersion process, the average length of the CNT bundles decreases by increasing the pressure applied to the mixed liquid passing through the jet mill, and increases by decreasing the pressure. In addition, the average length of the CNT bundles in the CNT dispersion can be decreased by increasing the number of passes of the dispersion process using the wet jet mill (the number of times the entire mixed liquid passes through the wet jet mill), and increases by decreasing the number of passes.

[0023] [Average diameter] The average diameter of the CNT bundle must be 18.0 nm or less, preferably 17.5 nm or less, more preferably 17.0 nm or less, even more preferably 16.5 nm or less, even more preferably 16.0 nm or less, and particularly preferably 15.5 nm or less. If the average diameter of the CNT bundle exceeds 18.0 nm, the stability of the dispersion state of the CNT dispersion liquid over time decreases, and the conductivity of the obtained molded body decreases. In addition, the lower limit of the average diameter of the CNT bundle is not particularly limited, and can be, for example, 13.5 nm or more, or 14.0 nm or more. The average diameter of the CNT bundles in the CNT dispersion can be adjusted, for example, by changing the diameter of the raw CNTs and the conditions of the dispersion process. For example, when a wet jet mill is used for the dispersion process, the average diameter of the CNT bundles decreases by increasing the pressure applied to the mixed liquid passing through the wet jet mill, and increases by decreasing the pressure. In addition, the average diameter of the CNT bundles in the CNT dispersion decreases by increasing the number of passes of the dispersion process using the wet jet mill, and increases by decreasing the number of passes.

[0024] [Number of CNT bundles with diameters over 30.0 nm] The number of CNT bundles having a diameter of more than 30.0 nm must be 15 or less, preferably 14 or less, more preferably 13 or less, even more preferably 12 or less, even more preferably 11 or less, and particularly preferably 10 or less. If the number of CNT bundles having a diameter of more than 30.0 nm is more than 15, the stability of the dispersion state of the CNT dispersion over time decreases, and the conductivity of the resulting molded body decreases. In addition, the lower limit of the number of CNT bundles having a diameter of more than 30.0 nm is not particularly limited, and can be, for example, 1 or more, or 2 or more. The number of CNT bundles with diameters exceeding 30.0 nm can be adjusted, for example, by changing the length or diameter of the raw CNTs and the conditions of the dispersion process. For example, when a wet jet mill is used for the dispersion process, increasing the pressure applied to the mixed liquid passing through the wet jet mill reduces the number of CNT bundles with diameters exceeding 30.0 nm, and decreasing the pressure increases the number. In addition, increasing the number of passes of the dispersion process using the wet jet mill reduces the number of CNT bundles with diameters exceeding 30.0 nm, and decreasing the number increases the number.

[0025] [Average aspect ratio] The average aspect ratio of the CNT bundle is preferably more than 100, more preferably 110 or more, even more preferably 120 or more, even more preferably 130 or more, and particularly preferably 135 or more. If the average aspect ratio of the CNT bundle is more than 100, the stability of the dispersion state of the CNT dispersion over time can be further improved, and the conductivity of the molded body can be further increased. In addition, the upper limit of the average aspect ratio of the CNT bundle is not particularly limited, and can be, for example, 250 or less, 225 or less, or 200 or less.

[0026] [G / D ratio] The G / D ratio of the CNTs is preferably 0.5 or more, more preferably 1 or more, and is preferably 120 or less, more preferably 110 or less, even more preferably 95 or less, even more preferably 70 or less, even more preferably 45 or less, and particularly preferably 20 or less. If the G / D ratio of the CNTs is within the above-mentioned range, the stability over time of the dispersed state of the CNT dispersion can be further improved, and the conductivity of the molded body can be further increased.

[0027] <<Content ratio>> The content of CNT in the CNT dispersion is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, even more preferably 0.2% by mass or more, preferably 2% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less, based on the total amount of the CNT dispersion being 100% by mass. If the proportion of CNT in the CNT dispersion is 0.01% by mass or more, the conductivity of the molded body can be further increased and the productivity of the molded body can be improved. On the other hand, if the proportion of CNT in the CNT dispersion is 2% by mass or less, the stability of the dispersion state of the CNT dispersion over time can be further improved.

[0028] <Solvent> The CNT dispersion of the present invention may contain only water as a solvent, may contain only an organic solvent (e.g., esters, ketones, alcohols) as a solvent, or may be a mixture of water and an organic solvent. From the viewpoint of further improving the stability of the dispersion state of the CNT dispersion over time while further increasing the conductivity of the molded body, it is preferable that the CNT dispersion of the present invention contains water as a solvent. The CNT dispersion of the present invention may contain one type of organic solvent, or may contain two or more types of organic solvents.

[0029] Here, the CNT dispersion of the present invention preferably has a water ratio in the solvent of 70 mass% or more, more preferably 90 mass% or more, even more preferably 99 mass% or more, and particularly preferably 100 mass% (i.e., the CNT dispersion of the present invention contains only water as a solvent), with the total amount of the solvent being 100 mass%. If the water ratio in the solvent in the CNT dispersion is equal to or more than the lower limit, the stability over time of the dispersion state of the CNT dispersion can be further improved, and the conductivity of the molded body can be further increased.

[0030] <Thickener> The thickener is not particularly limited and may be any known thickener, and may be, for example, a water-soluble polymer such as a cellulose-based polymer, a polycarboxylic acid, or a water-soluble vinyl polymer. In the present invention, a polymer is "water-soluble" means that when 0.5 g of the polymer (solid content) is dissolved in 100 g of water at 25°C, the amount of insoluble matter is less than 10.0 mass %.

[0031] Cellulosic polymers include, for example, carboxymethylcellulose, methylcellulose, hydroxypropylmethylcellulose, hydroxyethylmethylcellulose, and salts and derivatives thereof. Polycarboxylic acids include, for example, polyacrylic acid, polymethacrylic acid, alginic acid, and salts and derivatives thereof. Examples of the water-soluble vinyl polymer include polyvinylpyrrolidone, polyvinyl alcohol, polyvinyl methyl ether, poly-N-vinylacetamide, polyacrylamide, and polyimide. Here, examples of the salt include alkali metal salts such as sodium salts, ammonium salts, etc. Examples of the derivative include esters such as alkyl esters, and ethers.

[0032] The above-mentioned thickeners may be used alone or in any combination of two or more at any ratio. Among these, from the viewpoint of further improving the stability over time of the dispersion state of the CNT dispersion and further increasing the conductivity of the molded body, the thickeners are preferably cellulose-based polymers, polycarboxylic acids, and polyvinylpyrrolidone, and more preferably carboxymethylcellulose and its salts, polyacrylic acid and its salts, and polyvinylpyrrolidone.

[0033] <<Weight average molecular weight>> The weight average molecular weight of the thickener is preferably 5,000 or more, more preferably 10,000 or more, and is preferably 1,000,000 or less, and more preferably 500,000 or less. If the weight average molecular weight of the thickener is 5,000 or more, the dispersibility of CNTs in the CNT dispersion can be improved. Also, if the weight average molecular weight of the thickener is 1,000,000 or less, the viscosity increase of the CNT dispersion can be suppressed. In the present invention, the "weight average molecular weight" can be measured using gel permeation chromatography and expressed as a standard polystyrene equivalent value.

[0034] <<Content ratio>> The ratio of the thickener contained in the CNT dispersion is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 2% by mass or less, based on the total amount of the CNT dispersion being 100% by mass. If the ratio of the thickener in the CNT dispersion is within the above-mentioned range, the stability over time of the dispersion state of the CNT dispersion can be further improved, and the conductivity of the molded body can be further increased.

[0035] The content of the thickener in the CNT dispersion is preferably 50 parts by mass or more, more preferably 100 parts by mass or more, preferably 500 parts by mass or less, more preferably 400 parts by mass or less, and even more preferably 300 parts by mass or less per 100 parts by mass of CNT. If the amount ratio of the thickener to CNT in the CNT dispersion is within the above range, the temporal stability of the dispersion state of the CNT dispersion can be further improved, and the conductivity of the molded body can be further enhanced.

[0036] <Other components> Examples of other components that the CNT dispersion may optionally contain include conductive materials other than CNT, polymer components other than the above-described thickener, antioxidants, resins, and the like. Note that the CNT dispersion may contain only one type of other component or two or more types of other components. The proportion of other components contained in the CNT dispersion is preferably 5% by mass or less, more preferably 1% by mass or less, even more preferably 0.5% by mass or less, still more preferably 0.1% by mass or less, and particularly preferably 0% by mass (that is, the CNT dispersion of the present invention does not contain other components), with the total amount of the CNT dispersion being 100% by mass.

[0037] <Preparation of CNT dispersion> The CNT dispersion of the present invention can be prepared, for example, by subjecting a mixture containing the above-mentioned CNT, a solvent, a thickener, and any other components to a dispersion treatment. The dispersion treatment is not particularly limited, and can be performed using a mixer such as a wet jet mill, a bead mill, a ball mill, a sand mill, a pigment disperser, a crusher, an ultrasonic disperser, a homogenizer, a planetary mixer, or a Filmix. Among them, it is preferable to use a wet jet mill from the viewpoint of further improving the stability of the dispersion state of the CNT dispersion over time while further increasing the conductivity of the molded body. Examples of wet jet mills include "NanoVeita (registered trademark)" (manufactured by Yoshida Machine Co., Ltd.), "BERYU SYSTEM PRO" (manufactured by Biryu Co., Ltd.), ultra-high pressure wet atomizer (manufactured by Yoshida Kogyo Co., Ltd.), "Nanomizer (registered trademark)" (manufactured by Nanomizer Co., Ltd.), and "Starburst (registered trademark)" (manufactured by Sugino Machine Co., Ltd.).

[0038] Here, examples of the nozzles equipped in the wet jet mill include a straight nozzle and a cross nozzle. The straight nozzle has an I-shaped nozzle cross section and requires relatively small processing energy. On the other hand, the cross nozzle has an X-shaped nozzle cross section and requires larger processing energy than the straight nozzle. From the viewpoint of further improving the stability over time of the dispersion state of the CNT dispersion and further increasing the conductivity of the molded body, it is preferable to use a straight nozzle as the nozzle equipped in the wet jet mill.

[0039] Here, the pressure applied during the dispersion treatment of the mixed liquid by the wet jet mill is preferably 10 MPa or more, more preferably 20 MPa or more, even more preferably 40 MPa or more, and preferably 200 MPa or less, more preferably 150 MPa or less. If the pressure applied to the mixed liquid is 10 MPa or more, the stability of the dispersion state of the CNT dispersion over time can be further improved and the conductivity of the resulting molded body can be further increased. In addition, if the pressure applied to the mixed liquid is 200 MPa or less, the cutting of the CNTs due to the dispersion treatment can be suppressed, thereby further increasing the conductivity of the resulting molded body.

[0040] In addition, the number of passes of the dispersion treatment by the wet jet mill is preferably 10 or more, more preferably 15 or more, and preferably 100 or less, more preferably 80 or less, and even more preferably 60 or less. If the number of passes of the dispersion treatment by the wet jet mill is 10 or more, the stability of the dispersion state of the CNT dispersion over time can be further improved and the conductivity of the obtained molded body can be further increased. In addition, if the number of passes of the dispersion treatment by the wet jet mill is 100 or less, the cutting of the CNTs due to the dispersion treatment can be suppressed, thereby further increasing the conductivity of the obtained molded body and sufficiently ensuring the production efficiency of the CNT dispersion. EXAMPLES

[0041] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples. In the following description, "%" and "parts" expressing amounts are based on mass unless otherwise specified. In the examples and comparative examples, the average length, average diameter, average aspect ratio, and number of CNT bundles with a diameter of more than 30.0 nm when observed with an SEM, the average length of the CNT bundles, the G / D ratio of the CNTs, the rate of change in particle size, and the rate of change in viscosity when observed with an optical microscope, and the volume conductivity of the carbon film (molded body) were evaluated by the following methods.

[0042] <Average length, average diameter, average aspect ratio (SEM)> The CNT dispersion liquid prepared in the examples and comparative examples was diluted with pure water so that the CNT concentration was 25 ppm by mass. After dropping one drop of the obtained diluted solution onto the wafer with a dropper, the wafer was placed on a hot plate heated to 90°C and baked for 1 minute. The obtained CNT-coated wafer was observed using a scanning electron microscope (SEM, Hitachi High-Tech Corporation, product name "SU8200") under conditions of a working distance of 3 mm, an acceleration voltage of 1.0 kV, and a magnification of 10,000 times, and multiple SEM images containing 10 or more CNT bundles within the field of view were obtained. The diameter (outer diameter) and length of the bundle were measured for 100 CNT bundles arbitrarily extracted from the obtained SEM images. The arithmetic average value of the diameters of the measured 100 CNT bundles was taken as the average diameter (nm) of the CNT bundles in the CNT dispersion liquid. The arithmetic mean of the lengths of the 100 measured CNT bundles was taken as the average length (μm) of the CNT bundles in the CNT dispersion. The average aspect ratio was calculated by dividing the average length (nm) by the average diameter (nm). <Number of CNT bundles with diameters over 30.0 nm> As described above, the diameters (outer diameters) of 100 CNT bundles were measured using SEM and evaluated according to the following criteria. A: 10 or less fibers with a diameter of 30.0 nm or more B: 11 to 15 fibers with a diameter of 30.0 nm or more C: 16 or more fibers with diameters over 30.0 nm <Average length (optical microscope)> The CNT dispersions prepared in the examples and comparative examples were diluted to 0.02% with pure water. A drop of the resulting diluted solution was placed on a glass slide with a dropper, and then the glass slides were sandwiched between the glass slides and observed at a magnification of 700x using a digital microscope (manufactured by Keyence Corporation, product name "VHX-7000"). The lengths of all CNT bundles observed in one field of view were measured, and the arithmetic mean value was taken as the average length (μm) of the CNT bundles, and the results were evaluated according to the following criteria. A: Average length is 15.0 μm or more B: Average length is 8.0 μm or more and less than 15.0 μm C: Average length less than 8.0 μm <G / D ratio> Using a microscopic laser Raman spectrophotometer (manufactured by Thermo Fisher Scientific, product name "Nicolet Almega XR"), the Raman spectra of the CNTs used in the examples and comparative examples were measured. Then, regarding the obtained Raman spectra, the intensity of the G-band peak observed near 1590 cm -1 and the intensity of the D-band peak observed near 1340 cm -1 were determined, and the G / D ratio was calculated. <Temporal stability of the dispersion state> If both the "particle size change rate" and "viscosity change rate" shown below are evaluated as A or B, it means that the CNT dispersion has excellent temporal stability of the dispersion state. [Particle size change rate] Regarding the CNT dispersions obtained in the examples and comparative examples, the values of the average particle size (D50) immediately after preparation and the values of the average particle size (D50) 10 days after preparation were measured respectively. The average particle size (D50) was measured with a laser diffraction / scattering particle size distribution measuring device (manufactured by HORIBA, product name "Partica LA-960V2") for an aqueous dispersion diluted with water so that the CNT concentration became 0.04%. In the obtained particle size distribution (volume basis), the particle size at which the cumulative volume calculated from the small diameter side became 50% was determined as the average particle size (μm). The measurement conditions were as follows. · Circulation speed: 3, ultrasonic intensity: 7, ultrasonic time: 1 minute, stirring speed: 1, stirring mode: continuous (operation conditions of circulation / ultrasonic) · Ultrasonic intensity 7, ultrasonic time 5 seconds (ultrasonic operation during air evacuation) · Refractive index of water: 1.333 · Refractive index of carbon material: 1.92 Then, taking the value of the average particle size (D50) immediately after preparation as d0 (μm) and the value of the average particle size (D50) 10 days after preparation as d1 (μm), the particle size change rate (%) = [(d1 - d0) / d0] × 100 was used to calculate the particle size change rate (%), and it was evaluated according to the following criteria. The smaller the value of the particle size change rate, the more difficult it is for the dispersion state of the CNTs to change, that is, it means that the temporal stability of the dispersion state is excellent. A: Particle size change rate is less than 1% B: Particle size change rate is 1% or more and less than 30% C: Particle size change rate is 30% or more [Viscosity change rate] For the CNT dispersions obtained in the examples and comparative examples, the viscosity values immediately after preparation and the viscosity values 10 days after preparation were measured respectively. Each viscosity measurement was performed at a temperature of 20 °C using a rheometer (manufactured by Anton Paar, product name "MCR-102"). Specifically, a cone plate was used as the measurement jig, the range of shear rate from 100 to 9000 (1 / s) was measured, and the viscosity (mPa·s) at a shear rate of 1000 (1 / s) was determined. Then, taking the viscosity value immediately after preparation as η0 (mPa·s) and the viscosity value 10 days after preparation as η1 (mPa·s), the viscosity change rate (%) = [(η1 - η0) / η0] × 100 was used to calculate the viscosity change rate (%), and the evaluation was carried out according to the following criteria. The smaller the value of the viscosity change rate, the less likely the CNT dispersion is to thicken over time, that is, it means that the dispersion state has excellent temporal stability. A: Viscosity change rate is less than 10% B: Viscosity change rate is 10% or more and less than 20% C: Viscosity change rate is 20% or more <Volume conductivity> The volume conductivity (S / cm) of the carbon films (formed bodies) prepared in the examples and comparative examples was measured using a low resistivity meter (manufactured by Mitsubishi Chemical Analytech Co., Ltd., product name "Roresta-GX") in accordance with JIS K 7194, and the evaluation was carried out according to the following criteria. The higher the value of this volume conductivity, the more excellent the conductivity of the carbon film (formed body). A: Value of volume conductivity is 100 S / cm or more B: Value of volume conductivity is 50 S / cm or more and less than 100 S / cm C: Value of volume conductivity is less than 50 S / cm

[0043] (Example 1) <Preparation of CNT dispersion> [Synthesis of CNT] According to the method disclosed in Example 4 of WO 2022 / 114237, a single-walled CNT (hereinafter referred to as "CNT-a") was produced. The properties of the obtained CNT-a were G / D ratio: 1.2, tapped bulk density: 0.02 g / cm 3 , CNT average length: 150 μm, BET specific surface area: 600 m 2 / g, average outer diameter: 4.0 nm, and carbon purity: 99.0 mass %. [Preparation of CNT dispersion] 1.2 g of CNT-a (G / D ratio: 1.2) as the single-walled CNT obtained above was added to 300 mL of an aqueous solution (concentration of sodium carboxymethylcellulose: 0.4%) containing sodium carboxymethylcellulose (manufactured by Tokyo Chemical Industry Co., Ltd., product code "C0045"; average degree of polymerization: 500) as a thickener in water as a solvent, to obtain a mixed liquid (concentration of single-walled CNT: 0.4%). A dispersion treatment was performed on this mixed liquid using a wet jet mill (manufactured by Yoshida Kikai Kogyo Co., Ltd., model number "NVL-ES008A-D10", product name "Nano Vaita (registered trademark)") under conditions of a pressure of 50 MPa and a number of passes of 40. Specifically, a shear force was applied to the mixed liquid while applying back pressure to disperse the single-walled CNT, and a CNT dispersion liquid was obtained. The average length, average diameter, average aspect ratio, and number of CNT bundles with a diameter of more than 30.0 nm were measured for the obtained CNT dispersion by SEM observation, and the average length of the CNT bundles by optical microscope observation, as well as the rate of change in particle diameter and the rate of change in viscosity. The results are shown in Table 1. <Preparation of carbon film (molded body)> The CNT dispersion liquid prepared above was filtered under a condition of 0.09 MPa using a vacuum filtration device equipped with a membrane filter. After the filtration was completed, the carbon film formed on the membrane filter was washed by passing isopropyl alcohol and water through the vacuum filtration device, and then air was passed through for 15 minutes. Next, the carbon film / membrane filter was immersed in ethanol, and the carbon film was peeled off from the membrane filter to obtain a carbon film as a molded body. The obtained carbon film was the same size as the membrane filter and had excellent film forming properties, and even when peeled off from the filter, it maintained its film state and had excellent self-supporting properties. The volume conductivity of this carbon film was measured. The results are shown in Table 1.

[0044] (Examples 2 to 8, Comparative Examples 1 to 6) During the preparation of the CNT dispersion, the pressure and number of passes in the dispersion treatment using a wet jet mill were changed as shown in Tables 1 and 3, but the preparation of the CNT dispersion and the production of the carbon film were carried out in the same manner as in Example 1. Then, evaluation was carried out in the same manner as in Example 1. The results are shown in Tables 1 and 3.

[0045] (Examples 9 to 11) During the preparation of the CNT dispersion, the concentration of the aqueous sodium carboxymethylcellulose solution was changed from 0.4% to 0.8%, and the pressure and number of passes in the dispersion treatment using the wet jet mill were changed as shown in Table 1. Except for this, the synthesis of CNTs, the preparation of the CNT dispersion, and the production of the carbon film were carried out in the same manner as in Example 1. Then, evaluation was carried out in the same manner as in Example 1. The results are shown in Table 1.

[0046] (Examples 12 to 14) During the preparation of the CNT dispersion, the concentration of the aqueous sodium carboxymethylcellulose solution was changed from 0.4% to 1.2%, and the pressure and number of passes in the dispersion treatment using the wet jet mill were changed as shown in Table 2. Except for this, the synthesis of CNTs, the preparation of the CNT dispersion, and the production of the carbon film were carried out in the same manner as in Example 1. Then, evaluation was carried out in the same manner as in Example 1. The results are shown in Table 2.

[0047] Example 15 Synthesis of CNTs, preparation of CNT dispersions, and fabrication of carbon films were carried out in the same manner as in Example 1, except that sodium polyacrylate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., product code "196-02955"; degree of polymerization: 22,000 to 70,000) was used instead of sodium carboxymethylcellulose as a thickener when preparing the CNT dispersion. Evaluations were then carried out in the same manner as in Example 1. The results are shown in Table 2.

[0048] (Example 16) The synthesis of CNTs, the preparation of a CNT dispersion, and the production of a carbon film were carried out in the same manner as in Example 1, except that polyvinylpyrrolidone (manufactured by Nippon Shokubai Co., Ltd., product name "Polyvinylpyrrolidone-K30"; HLB value: 15) was used instead of sodium carboxymethylcellulose as a thickener when preparing the CNT dispersion. Evaluations were then carried out in the same manner as in Example 1. The results are shown in Table 2.

[0049] (Example 17) During preparation of the CNT dispersion, CNT-b (manufactured by Zeon Corporation, product name "ZEONANO (registered trademark) SG101"; G / D ratio: 5.0) was used instead of CNT-a as single-walled CNT, and the pressure and number of passes in the dispersion treatment using a wet jet mill were changed as shown in Table 2. Except for this, the preparation of the CNT dispersion and the production of the carbon film were carried out in the same manner as in Example 1. Then, evaluation was carried out in the same manner as in Example 1. The results are shown in Table 2.

[0050] (Examples 18 to 19) During preparation of the CNT dispersion, CNT-c (manufactured by OCSiAl, product name "Tuball (registered trademark)"; G / D ratio: 109) was used instead of CNT-a as the single-walled CNT, and the pressure and number of passes in the dispersion treatment using the wet jet mill were changed as shown in Table 2. Except for this, the preparation of the CNT dispersion and the production of the carbon film were carried out in the same manner as in Example 1. Then, evaluation was carried out in the same manner as in Example 1. The results are shown in Table 2.

[0051] (Examples 20 to 21) During preparation of the CNT dispersion, CNT-d (manufactured by Meijo Nano Carbon Co., Ltd., product name "MEIJO eDIPS (registered trademark)"; G / D ratio: 119) was used instead of CNT-a as the single-walled CNT, and the pressure and number of passes in the dispersion treatment using the wet jet mill were changed as shown in Table 2. Except for this, the preparation of the CNT dispersion and the production of the carbon film were carried out in the same manner as in Example 1. Then, evaluation was carried out in the same manner as in Example 1. The results are shown in Table 2.

[0052] Comparative Example 7 The synthesis of CNTs, the preparation of CNT dispersions, and the production of carbon films were carried out in the same manner as in Example 1, except that the amount of CNT-a used was changed from 1.2 g to 0.3 g during the preparation of the CNT dispersion. Evaluations were then carried out in the same manner as in Example 1. The results are shown in Table 3. Note that the dispersibility of CNTs in the CNT dispersion was extremely low, and the average length and average diameter of the CNT bundles observed with SEM could not be measured.

[0053] In addition, in Tables 1 to 3 shown below, "SEM" stands for scanning electron microscope; "OM" stands for optical microscope; "Single-walled" refers to single-walled CNTs; "CMC" stands for sodium carboxymethylcellulose; "PAA" stands for sodium polyacrylate; "PVP" refers to polyvinylpyrrolidone; "Number of CNT bundles with a diameter of more than 30 nm" indicates the number of CNT bundles with a diameter of more than 30.0 nm out of 100 CNT bundles. In addition, the "average aspect ratio of the CNT bundle" is expressed as a value rounded off to the first decimal place.

[0054] [Table 1]

[0055] [Table 2]

[0056] [Table 3]

[0057] As can be seen from Tables 1 to 3, in Examples 1 to 21 which used CNT dispersions containing single-walled CNTs, a solvent, and a thickener, and in which the average length of the CNT bundles exceeds a predetermined value, the average diameter of the CNT bundles is equal to or less than a predetermined value, and the number of CNT bundles having a diameter of more than 30.0 nm out of 100 CNT bundles is equal to or less than a predetermined value, and the average length of the CNT bundles is equal to or more than a predetermined value when observed with an optical microscope, it is possible to produce CNT dispersions with excellent stability of the dispersed state over time and carbon films with excellent electrical conductivity. On the other hand, in Comparative Examples 1 to 2 and 4, in which the average diameter and the number of CNT bundles with a diameter exceeding 30.0 nm each exceed the specified value, and in Comparative Example 7, in which the number of CNT bundles with a diameter exceeding 30.0 nm exceeds the specified value, it can be seen that the stability of the dispersion state of the CNT dispersion over time and the conductivity of the carbon film are reduced compared to Examples 1 to 21. Furthermore, it can be seen that the conductivity of the carbon film is reduced in Comparative Example 3, in which the average length observed with an optical microscope is less than the predetermined value, and in Comparative Examples 5 and 6, in which the average length observed with an SEM is equal to or less than the predetermined value, compared to Examples 1 to 21. [Industrial Applicability]

[0058] According to the present invention, it is possible to provide a carbon nanotube dispersion liquid which is excellent in the stability of the dispersed state over time and is capable of forming a molded body having excellent electrical conductivity.< / cnt>

Claims

1. A carbon nanotube dispersion liquid containing a plurality of carbon nanotubes, a solvent, and a thickener, the plurality of carbon nanotubes includes single-walled carbon nanotubes; At least a portion of the plurality of carbon nanotubes form a carbon nanotube bundle; When the carbon nanotube bundle is observed with a scanning electron microscope, the average length of the carbon nanotube bundle is more than 1.50 μm, the average diameter of the carbon nanotube bundle is 18.0 nm or less, and the number of carbon nanotube bundles having a diameter of more than 30.0 nm is 15 or less out of 100 carbon nanotube bundles; The carbon nanotube dispersion liquid, wherein the carbon nanotube bundles have an average length of 8.0 μm or more when observed under an optical microscope.

2. The carbon nanotube dispersion of claim 1 , wherein the carbon nanotube bundles have an average aspect ratio of greater than 100.

3. The carbon nanotube dispersion according to claim 1 , wherein the G / D ratio of the carbon nanotubes is 0.5 or more and 120 or less.

4. 4. The carbon nanotube dispersion according to claim 1, wherein the thickener comprises at least one selected from the group consisting of a cellulose-based polymer, a polycarboxylic acid, and a polyvinylpyrrolidone.

Citation Information

Patent Citations

  • Carbon nanotube dispersion liquid for non-aqueous electrolyte secondary battery, resin composition using the same, mixture slurry, electrode film, and non-aqueous electrolyte secondary battery

    JP2021072279A

  • Carbon nanotube dispersion and usage therefor

    WO2020004095A1